Interaction of Ht and Partial Resistance to Exserohilum turcicum in Maize - Lipps, P. E.; Pratt, R. C.; Hakiza, J. J. (Plant disease, 1997)
Components of northern leaf blight resistance in maize due to race-specific resistance controlled by the Ht gene, partial resistance derived from inbred H99, and a combination of the two kinds of resistance, were studied subsequent to inoculation with Exserohilum turcicum race O. Lesion types, number of lesions (lesion number), percent leaf area affected (severity), and area under the disease progress curve (AUDPC) based on lesion number and severity were assessed in field studies conducted at two locations in Uganda and one location in Ohio in 1993. Lesion types observed were consistent for genotypes across locations. In general, significant differences among genotypes for data based on lesion number and severity were consistent for AUDPC based on lesion number and severity, respectively, at all locations. In Ohio, both Ht and partial resistance were effective in limiting disease development. In Uganda, susceptible inbreds (A619, A635, and B73) generally had higher severity than genotypes with partial resistance (H99, Mo17, and Babungo 3). However, there was a difference in response among genotypes depending on disease intensity at each location. Ht resistance and moderate partial resistance did not greatly affect lesion number at the higher disease intensity location, compared with the susceptible inbreds, but at the lower disease intensity location genotypes with partial resistance had fewer lesions than susceptible inbreds or the Ht conversions of the susceptible inbreds. At both plot locations, genotypes with partial resistance had lower severity than the susceptible inbreds or Ht conversions of the susceptible inbreds. Hybrids derived from crossing H99 with genotypes with moderate levels of partial resistance (Mo17 and Babungo 3) did not have significantly lower lesion numbers than hybrids of susceptible inbreds crossed with H99, but severity was significantly lower on these hybrids at the high disease intensity location. Results indicate that the level of partial resistance in H99 would be as effective in controlling northern leaf blight as using Ht resistance, or a combination of Ht resistance and moderate levels of partial resistance as found in Mo17.
Keywords: Maize; Exserohilum turcicum; Ht and Partial Resistance